Students’ perceptions on teachers’ feedback - Subedi, Kusum Raj; Subedi, Suprabha (Shaheed Smriti Journal, 2022)
Feedback is prescribed information given to the targeted learner about the learner's performance relative to learning goals or outcomes. It should aim to (and be capable of producing) improvement in students' learning. Similarly, it redirects or refocuses the learner's actions to achieve a goal, by aligning effort and activity with an outcome. The purpose of this study is to describe ‘Students’ Perceptions on Teachers’ Feedback’ on Homework’ aimed at analyzing students’ perceptions towards their teachers’ written and oral feedbacks and exploring the feedback techniques used by teachers in class eight. This study was carried out using both the primary and secondary sources of data. For primary data, sixty students were randomly selected from four schools of Chitwan District. I used both the closed and open-ended questions to elicit the required data. It was found that the students would like to get positive feedback for homework from their teachers. Majority of the students’ perceived teachers’ feedback on homework is extremely helpful to improve their performance in classrooms. The study also discovered that the general feedback techniques the teacher used in the classrooms were teacher correction, peer correction and self correction. The findings, conclusions and recommendations were made after the analysis of the data